Navigating Labor Dynamics Through the Lens of Islamic Economics - Ahmad Lukman Nugraha; Asri Sundari; Achmad Ridwan; Asti Meiza (Green Economics Review, 2024)
This study investigates the elasticity of labor absorption in an Indonesian city from an Islamic economics perspective, aiming to provide novel insights into the relationship between economic growth and employment dynamics. Employing quantitative methods, the research utilizes secondary data on employment rates from 2015 to 2019. The findings reveal that the elasticity of employment in 2015 was 0.95, categorizing it as inelastic. Notably, in 2016, employment elasticity turned negative, indicating an inverse relationship between economic growth and employment growth. The year 2017 saw a dramatic increase in employment growth from -19.03% to 30.6%, despite a decline in economic growth of 5.43%. This resulted in an elasticity value of 5.63, placing it in the elastic category, where the growth rate of employment exceeded that of the economy. In contrast, the elasticity in 2018 returned to 0.02, and by 2019, it was again negative, reinforcing the inverse relationship. Overall, the study finds that labor elasticity in this city predominantly fell within the inelastic category throughout the period analyzed, with significant elasticity observed only in 2017. These findings have important implications for policymakers, suggesting a need for targeted strategies that enhance labor absorption during periods of economic downturn, especially from an Islamic economic perspective, which emphasizes equitable employment growth and social welfare.